Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's solve the problem step-by-step:
1. Determine the slope of line \( \overleftrightarrow{A B} \):
The coordinates are \( A = (14, -1) \) and \( B = (2, 1) \).
The formula for the slope \(m\) between two points \((x_1, y_1)\) and \((x_2, y_2)\) is:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Here,
[tex]\[ m = \frac{1 - (-1)}{2 - 14} = \frac{2}{-12} = -\frac{1}{6} \][/tex]
So, the slope of \( \overleftrightarrow{A B} \) is \(-\frac{1}{6}\).
2. Find the y-intercept of line \( \overleftrightarrow{A B} \):
The equation of a line in slope-intercept form is \( y = mx + c \). We already have \( m = -\frac{1}{6} \).
To find \( c \) (the y-intercept), we use the point \( B \) which is \((2, 1)\):
[tex]\[ 1 = -\frac{1}{6} \cdot 2 + c \][/tex]
Simplifying, we get:
[tex]\[ 1 = -\frac{1}{3} + c \implies c = 1 + \frac{1}{3} = \frac{4}{3} \][/tex]
So, the y-intercept is \(\frac{4}{3}\) and the equation of \( \overleftrightarrow{A B} \) is:
[tex]\[ y = -\frac{1}{6}x + \frac{4}{3} \][/tex]
3. Find the slope of line \( \overleftrightarrow{B C} \):
Since \( \overleftrightarrow{B C} \) is perpendicular to \( \overleftrightarrow{A B} \), the product of their slopes is \(-1\).
Let \( m_{BC} \) be the slope of \( \overleftrightarrow{B C} \). Then:
[tex]\[ m_{BC} \cdot \left( -\frac{1}{6} \right) = -1 \implies m_{BC} = 6 \][/tex]
Thus, the slope of line \( \overleftrightarrow{B C} \) is \( 6 \).
4. Determine the x-coordinate of point \( C \) given its y-coordinate is 13:
The equation of \( \overleftrightarrow{B C} \) can be written using the slope-intercept form and the point \( B = (2, 1) \):
[tex]\[ y - 1 = 6(x - 2) \][/tex]
Given \( y = 13 \):
[tex]\[ 13 - 1 = 6(x - 2) \][/tex]
Simplifying this equation:
[tex]\[ 12 = 6(x - 2) \implies 2 = x - 2 \implies x = 4 \][/tex]
So, the x-coordinate of point \( C \) is \( 4 \).
Now, let's fill in the boxes in the original problem statement accordingly:
If the coordinates of \( A \) and \( B \) are \( (14, -1) \) and \( (2, 1) \), respectively, the \( y \)-intercept of \( \overleftrightarrow{A B} \) is \( y = -\frac{1}{6}x + \frac{4}{3} \).
If the [tex]\( y \)[/tex]-coordinate of point [tex]\( C \)[/tex] is [tex]\( 13 \)[/tex], its [tex]\( x \)[/tex]-coordinate is [tex]\( 4 \)[/tex].
1. Determine the slope of line \( \overleftrightarrow{A B} \):
The coordinates are \( A = (14, -1) \) and \( B = (2, 1) \).
The formula for the slope \(m\) between two points \((x_1, y_1)\) and \((x_2, y_2)\) is:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Here,
[tex]\[ m = \frac{1 - (-1)}{2 - 14} = \frac{2}{-12} = -\frac{1}{6} \][/tex]
So, the slope of \( \overleftrightarrow{A B} \) is \(-\frac{1}{6}\).
2. Find the y-intercept of line \( \overleftrightarrow{A B} \):
The equation of a line in slope-intercept form is \( y = mx + c \). We already have \( m = -\frac{1}{6} \).
To find \( c \) (the y-intercept), we use the point \( B \) which is \((2, 1)\):
[tex]\[ 1 = -\frac{1}{6} \cdot 2 + c \][/tex]
Simplifying, we get:
[tex]\[ 1 = -\frac{1}{3} + c \implies c = 1 + \frac{1}{3} = \frac{4}{3} \][/tex]
So, the y-intercept is \(\frac{4}{3}\) and the equation of \( \overleftrightarrow{A B} \) is:
[tex]\[ y = -\frac{1}{6}x + \frac{4}{3} \][/tex]
3. Find the slope of line \( \overleftrightarrow{B C} \):
Since \( \overleftrightarrow{B C} \) is perpendicular to \( \overleftrightarrow{A B} \), the product of their slopes is \(-1\).
Let \( m_{BC} \) be the slope of \( \overleftrightarrow{B C} \). Then:
[tex]\[ m_{BC} \cdot \left( -\frac{1}{6} \right) = -1 \implies m_{BC} = 6 \][/tex]
Thus, the slope of line \( \overleftrightarrow{B C} \) is \( 6 \).
4. Determine the x-coordinate of point \( C \) given its y-coordinate is 13:
The equation of \( \overleftrightarrow{B C} \) can be written using the slope-intercept form and the point \( B = (2, 1) \):
[tex]\[ y - 1 = 6(x - 2) \][/tex]
Given \( y = 13 \):
[tex]\[ 13 - 1 = 6(x - 2) \][/tex]
Simplifying this equation:
[tex]\[ 12 = 6(x - 2) \implies 2 = x - 2 \implies x = 4 \][/tex]
So, the x-coordinate of point \( C \) is \( 4 \).
Now, let's fill in the boxes in the original problem statement accordingly:
If the coordinates of \( A \) and \( B \) are \( (14, -1) \) and \( (2, 1) \), respectively, the \( y \)-intercept of \( \overleftrightarrow{A B} \) is \( y = -\frac{1}{6}x + \frac{4}{3} \).
If the [tex]\( y \)[/tex]-coordinate of point [tex]\( C \)[/tex] is [tex]\( 13 \)[/tex], its [tex]\( x \)[/tex]-coordinate is [tex]\( 4 \)[/tex].
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.